Phenylalanine ammonia-lyase 2 regulates secondary metabolism and confers manganese tolerance in Stylosanthes guianensis - Wang, Linjie; Li, Jifu; Liu, Liting; Dong, Rongshu; Liu, Guodao; Idupulapati, Rao; Chen, Zhijian (Oxford University Press, 2024)
Stylo (Stylosanthes guianensis) is a tropical legume that exhibits considerable tolerance to manganese (Mn) toxicity, which severely constrains plant growth in acidic soils. To elucidate the Mn detoxification mechanisms in stylo, this study investigated the excess Mn-regulated metabolic profile of stylo roots and examined the role of metabolic enzymes in Mn tolerance. Excess Mn triggered oxidative stress in the 2 stylo genotypes tested. However, Mn-stimulated activation of antioxidant defense systems was observed in the Mn-tolerant genotype RY5 but not in the Mn-sensitive genotype TF0317. Metabolomic analysis of the Mn-tolerant RY5 roots revealed numerous excess Mn-responsive metabolites, mainly related to flavonoids and phenolic acids. Furthermore, a set of genes involved in the phenylpropanoid/flavonoid pathway were upregulated by excess Mn in stylo roots, especially in RY5. We characterized the excess Mn-inducible gene SgPAL2, encoding phenylalanine ammonia-lyase. SgPAL2 localized to the endoplasmic reticulum. Compared with control plants, SgPAL2 overexpression led to increases in shoot and root dry weights under Mn-excess conditions, whereas SgPAL2 suppression had the opposite effect. Moreover, SgPAL2 overexpression dramatically altered secondary metabolism, particularly flavonoid metabolism. In a bioassay, the inhibition of root elongation caused by excess Mn was alleviated by treatment with exogenous calycosin, an SgPAL2-regulated isoflavonoid, suggesting calycosin can detoxify Mn. Taken together, these findings indicate that SgPAL2 plays a critical role in enhancing Mn tolerance in stylo through metabolic regulation.